Thol Tamil Samugathil Palli Sol Keatal - P, Kalaiselvan (International Research Journal of Tamil, 2021)
Different beliefs and practices are found in human life from birth to death. These beliefs are created by the people and are followed and protected by the mother’s community. Man has been living with nature since ancient times. Beliefs appeared in natural human life. Hope can be traced back to ancient Tamils and still prevails in Tamil Nadu today. The hope of seeing the omen in it is found all over the world. Proverbs show that people have faith in omens. Our ancestors wrote the book ’Gauli Shastri’ because the lizard omen is very important in our society. The word lizard played a major role in Tamil life during the Sangam period. It is possible to know that people have lived by the benefit of the lizard. There is hope from the public that the sound of the lizard will predict what will happen next. The purpose of this article is to illustrate the lizard word that has been around for a long time in folklore.